2019
DOI: 10.1186/s12885-019-5513-8
|View full text |Cite
|
Sign up to set email alerts
|

A lung cancer patient with deep vein thrombosis:a case report and literature review

Abstract: Background Venous thromboembolism (VTE) is a common problem in cancer patients and the incidence is increasing, especially for patients with lung cancer. Common features of these patients, like advanced stage, male gender, old age and chemotherapy, are risk factors of VTE. Here we reported a case in which the patient with lung cancer developed deep vein thrombosis (DVT) when receiving chemotherapy. Case presentation A 53-year-old male who was diagnosed with lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It has been reported that patients with advanced lung adenocarcinoma are predisposed to DVT, and tumor grade may help identify patients with cancer who are at a high risk of DVT. 15 Compared with patients in the primary stage, advanced cancer patients have a relatively shortened clotting time and increased plasminogen activator inhibitor level, 4 which may be related to the higher risk of DVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that patients with advanced lung adenocarcinoma are predisposed to DVT, and tumor grade may help identify patients with cancer who are at a high risk of DVT. 15 Compared with patients in the primary stage, advanced cancer patients have a relatively shortened clotting time and increased plasminogen activator inhibitor level, 4 which may be related to the higher risk of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines regarding the use of anticoagulants in lung cancer patients vary. 15 Specific therapeutic studies are needed to determine the optimal duration and dose of anticoagulant treatment in patients with cancer-related DVT.…”
Section: Discussionmentioning
confidence: 99%
“…As the second cause of death, VTE poses a significant comorbidity in cancer patients, and a common cause of hospitalizations, thereby significantly contributing to cancer-associated health care costs [ 117 ]. Several cancers are associated with increased VTE risk, including renal carcinoma [ 118 ]; hepatocellular carcinoma [ 119 ]; lung cancer [ 120 ]; and esophageal and stomach cancer [ 112 ]. Moreover, VTE in esophageal or gastric cancer patients has been associated with decreased survival: patient survival without VTE is 18 months compared with 13.9 months with VTE [ 121 ].…”
Section: Platelets In Cancer—“double-edged Sword”?mentioning
confidence: 99%
“…2 Lung cancer is one of the most prevalent types of malignant tumor and the main cause of cancer-related death worldwide. [3][4][5] After the onset of VTE, the 1-year mortality rate is as high as 61%. 6 The risk of VTE in lung cancer patients can be as high as 4% to 20%.…”
Section: Introductionmentioning
confidence: 99%